The truth about Stacey - Martin, Ann M., 1955- (New York : Scholastic, 1986)
Stacey, a member of the Baby-sitters Club, learns to cope with her diabetes and her overprotective parents.
"An Apple paperback.".
4.0
3-6
Keywords: Babysitters -- Fiction; Diabetes -- Fiction; Babysitters -- Fiction; Diabetes -- Fiction